2019
DOI: 10.1177/0032258x19855113
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to reporting hate crime: A Welsh perspective

Abstract: This study gathered 197 participants, interviewed within 48 hours of being victims of Hate Crime. This immediate follow-up should ensure accurate responses. The responses of the victims were compared to that of 113 Welsh front-line staff who respond to and support such victims. The barriers to reporting are found to be broadly similar with the findings of other UK studies. A considerable difference in understanding of the barriers to reporting hate crime was found between the victims and support services. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…From a community perspective, it is crucial to leverage community resources to enhance understanding of minority communities. This aligns with a recent study on hate crimes, where respondents emphasized the need for better advertisement of the reporting system, victim education and increased awareness of the topic and related issues (Cuerden and Blakemore, 2020). Clearer knowledge about hate crime definitions, reporting procedures and case processes is expected to foster mutual understanding between targeted communities and various stakeholders, ultimately contributing to increased reporting and a reduction in the fear of crime (Khondaker et al.…”
Section: Discussionsupporting
confidence: 85%
“…From a community perspective, it is crucial to leverage community resources to enhance understanding of minority communities. This aligns with a recent study on hate crimes, where respondents emphasized the need for better advertisement of the reporting system, victim education and increased awareness of the topic and related issues (Cuerden and Blakemore, 2020). Clearer knowledge about hate crime definitions, reporting procedures and case processes is expected to foster mutual understanding between targeted communities and various stakeholders, ultimately contributing to increased reporting and a reduction in the fear of crime (Khondaker et al.…”
Section: Discussionsupporting
confidence: 85%
“…In the broad, it has been established that hate incidents hurt more than parallel incidents without a bias motive, thus the type of incident is not related to the severity of emotional changes in victims (Ignaski, 2001;Nel & Mitchell, 2019). In relation, Cuerden and Blackmore (2020) found that the level of emotional impact is not differentiated by the type of hate incident. Thus, the type of incident does not predict individuals' experiencing emotional consequences among this particular cohort.…”
Section: Discussionmentioning
confidence: 95%
“…Christmann and Wong (2010), for example, found that victims were less likely to report to the police when the incident was less serious, primarily because they believed they would not be taken seriously by the police (see also Williams & Tregidga, 2013). Chakraborti et al (2014) also interviewed a number of hate crime victims who indicated that they would not report their victimization to the police because of a perception that police would not take it seriously or do anything to resolve the incident (see also Cuerden & Blakemore, 2020; Lantz et al, 2019).…”
Section: Reporting Victimization To the Policementioning
confidence: 99%